Criminal Failure and "The Chilling Effect": A Short History of the Bhopal Criminal Prosecutions - Edwards, Tim (Social justice, 2014)
The article focuses on the prosecution of those responsible for the Union Carbide pesticide plant disaster that occurred in Bhopal, India in 1984. Topics include the registration of Crime No. 1104/84 after the gas leak occurred, criminal justice administration in India, and corporate responsibility for industrial disasters.